Examining the effects of a mindfulness-based distance learning professional training module on personal and professional functioning: a qualitative study - Simon Whitesman; Robert Mash (BMC Medical Education, 2016)
Abstract Background Training people to deliver mindfulness-based interventions (MBI) is becoming an important activity as mindfulness has been shown to have clinical benefits across a variety of conditions. Training courses must not only address the principles, skills and theory of mindfulness, but the trainers themselves must be able to embody the practice. There is limited research on the ability of teachers-in-training to embody the practice as a result of teacher training programmes. This study explored the extent to which a short course enabled future teachers to embody mindfulness practice. This first module was part of a larger course of four modules to prepare future teachers of MBIs. Methods Qualitative data was obtained from 10 out of 35 end of course written assignments that asked respondents to reflect on their experience of mindfulness practice during the course. These were systematically selected and a focus group interview was also conducted with local participants. Data was analysed by means of the framework method and key themes identified. Results The combination of a retreat and on-line learning was perceived to be effective. Students reported significant changes in personal functioning as a result of daily mindfulness practice: self-awareness, improved relationships, enhanced connectedness, better self-regulation, enhanced compassion and curiosity towards self and others and self-acceptance. Participants began to introduce elements of mindfulness into their professional practice. Conclusions The first module of a post-graduate training programme for health professionals who want to teach MBIs successfully supported students to embody, explore and apply mindfulness in their lives. The integrated teaching modalities of residential retreat and distance-based on-line learning appeared effective.